An End-Stage Renal Disease Patient with Invasive Fungal Rhinosinusitis - Fatemeh Yassari; Nooshin Dalili; Farin Rashid farokhi; Mihan Pourabdollah (Archives of Clinical Nephrology - Peertechz Publications, 2017)
Mucormycosis is one of the invasive fungal infections particularly in immunocompromised patients with impaired host defense. It is characterized by fungal rhino sinusitis with invasion of adjustment structures including brain, pulmonary, or gastrointestinal systems or can be presented as a disseminated disease. Predisposing factors are diabetic ketoacidosis, neutropenia, corticosteroid or deferoxamine use, iron overload, malnutrition and skin macerations. We present a known case of end-stage renal disease patient under hemodialysis without history of diabetes or other risk factors listed above, who admitted because of fever and diagnosed with invasive rhino -sinusitis mucormycosis.